Pengaruh Kepercayaan Dan Kualitas Pelayanan Terhadap Minat Beli E - Commerce Lazada Di Surabaya - Indah Irawan; Hery Pudjoprastyono (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of trust and service quality on purchase intention on the site ecommerce lazada in Surabaya. This research includes quantitative research using primary data by distributing questionnaires to 60 respondents who are Lazada consumers in Surabaya. The population used in this research is all consumer usersEcommerce Lazada in Surabaya and the samples used were 60 consumers using E-Commerce Lazada in Surabaya. Sampling using purposive sampling technique. The data analysis technique in this study used PLS-SEM and data processing used the smartPLS 3.0 software program. Based on the test results, the greater consumer trust and service quality have a significant effect on purchase intention. Based on the hypothesis test, the variables of trust and service quality have a positive effect on consumer buying interest. It can be concluded that the higher the value of consumer trust and service quality, the consumer's buying interest will increase. Keywords : Consumer Trust, Service Quality, Repurchase Intention